Essays on Debt and Pensions - Henrik Yde Andersen (Copenhagen Business School (CBS), 2018)
Money is a scarce resource for most people. For that reason, the decision whether to spend more today and less in the future or vice versa is a recurrent question to many of us. Pension systems provide incentives for saving for future consumption and mortgage markets allow us to increase consumption immediately by giving up future spending opportunities accordingly. For this reason, pension and mortgage systems play a key role to individual savings decisions. This dissertation is comprised by three self-contained chapters concerned with how individual savings behavior depends on the design of certain pension and mortgage features.
hdl:10398/9627
Keywords: 650